Analisis Kinerja Algoritma Kriptografi Kandidat Advanced Encryption Standard (AES) pada Smartphone - Ahmad Farisi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2018)
Rijndael algorithm is the choosen algorithm for AES algorithm. However several previous studies have found the performance of rijndael algorithm on smartphones was under the other AES candidate algorithm such as serpent and twofish. This study compares the performance of rijndael, twofish, and serpent algorithms (the three major AES candidate algorithms) applied to smartphones. This study uses 3 devices with Android operating system and 3 devices with iOS operating system in the experiment. The experiments conducted in this study measure the performance of time, memory usage, and CPU percentage in the process of encryption and decryption performed using different key characters such as alphabet, numeric, alphanumeric, and alphanumeric and symbol. From 720 experiments conducted, this study found that serpent has the fastest time for encryption (0,025 ms) and decryption (0,022 ms). While the most efficient use of memory (0,032 KB) for encryption and decryption is done by twofish and rijndael. And the most efficient percentage of CPU usage (0,025 % for encryption and 0,038% for decryption) is done by serpent. The results of this experiment show that the performance of rijndael on smartphone is not better than other AES candidate algorithms, although the rijndael is the choosen AES algorithm